Applications of braided structures in civil engineering - Cunha, Fernando Eduardo Macedo (2016)
This chapter presents an overview of the applications of braided structures in civil engineering. A brief introduction is provided on fiber reinforced plastics (FRPs), different fibers, and polymeric resins used in civil construction. More specifically, this chapter discusses the utilization of braided structures in concrete reinforcement and masonry wall strengthening. Particular focus has been given on the recently developed braided composite rods (BCRs), and for each of these applications the technique for producing BCRs or BCR-based materials, application methods, and obtained results are discussed in detail. The comparison of performance of braided structures with that of conventional FRP-based materials is also presented in this chapter.